Strategic Ambiguity in Commodity Sales Contracts (GESTIÓN Y TENDENCIAS, 2023)
The research contrasts the approaches of classical contract theory and delegation theory to explain the existence of strategic ambiguity in commercial agreements. It emphasizes that, in commercial scenarios where the agent possesses expertise and informational advantages regarding final markets, drafting deliberately ambiguous or incomplete contracts prevents parties from diverting efforts toward distorted operational variables. By modeling a standard contract used in the commercialization of Chilean commodities to international markets, the study demonstrates that including asymmetric reliquidation clauses punishes and prevents moral hazard when an agent sells opaquely to related companies. The document theoretically illustrates that contractual ambiguity is not an error, but rather a strategic optimization tool in the face of manipulable transfer prices.
Keywords: Strategic Ambiguity; Delegation Theory; Transfer Pricing; Incomplete Contracts; Commodity Sales